The Relationship Between the Level of Knowledge and Community Attitudes in Facing Health Problems After the Flood Disaster in Pancuran Village, Bone Bolango Regency - Haslinda Damansyah; Susanti Monoarfa; Ferdi Mohi (PROMOTOR, 2024)
Disasters are a series of events that threaten people's lives and livelihoods, one form of disaster is flooding. Health problems that can arise can be in the form of infectious and non-communicable diseases such as skin diseases, diarrhea, ARI, and typhus abdominalis. The purpose of the research is to relationship knowledge with community attitudes in facing health problems after flood disasters—quantitative research design with a cross-sectional approach. The population of 69 people with the collection using the Sloving formula obtained a sample of 41 people. The results showed that the highest community knowledge studied in Pancuran Village was in the sufficient category of 15 people and the highest community attitude, was in the sufficient category of 22 people, pValue = 0.000<0.05 for community knowledge and pValue = 0.000<0.05 for community attitudes. The conclusion is that there is a relationship between knowledge and community attitudes in dealing with health problems after the flood disaster. Suggestions are expected to the village government and related puskesmas to continue to carry out counseling about floods and their impact on health in the community.